FACTORS INHIBITING THE IMPLEMENTATION OF THE OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT SYSTEM (HOSHMS) AT CILEGON CITY REGIONAL HOSPITAL - Afiah, Sri Amamal; Pertiwi, Wiwik Eko; Annissa, Annissa; Mathofani, Puji Eka (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Hospitals are one of the places that have a risk of occupational diseases and work accidents caused by various dangerous factors. The potential risk of disease or work accidents does not only occur to workers, patients but also to visitors and the community around the hospital. Therefore, hospitals are obliged to implement occupational safety and health through the management of the Hospital Occupational Safety and Health Management System (HOSHMS). This study aims to determine the relationship between inhibiting factors and the implementation of HOSHMS at Cilegon City Regional Hospital in 2023. The population in this study was all 335 nurses with a sample of 88 respondents. The samples were taken with proportional random sampling. The research design used is cross-sectional with chi square test at the level of significance (CI=95%, α=5%). The research data was collected through direct interviews using a questionnaire. The results of the analysis showed that there was no relationship between the quality of human resources and the implementation of OSHMS (p-value = 1.000) and no relationship between education and OSH training (p-value = 0.578) with the implementation of HOSHMS. In addition, there was a relationship between data management and OSH information (p value = 0.004) and a relationship between the implementation of law enforcement and the implementation of HOSHMS (p value = 0.012). Hospitals were advised to carry out a continuous OSH monitoring which is carried out in all work units and implement law enforcement more intensively.